Pengaruh Pemberian Employee Stock Option Program Terhadap Kinerja Perusahaan dengan Struktur Modal Sebagai Variabel Moderasi - Dewi, Gita Apsari; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 22 No 3 (2018), 2018)
Company performance is an important aspect seen by investors. The existence of the Employee Stock Option Program can enhance employees’s sense of belonging, which has an impact on improving the company's performance. The company needs additional funds from the creditor that is the capital structure. This may affect the giving of the Employee Stock Option Program. This study aims to obtain empirical evidence on the influence of capital structure in moderating the giving of Employee Stock Option Program to company performance. The sample used were 66 observations. The method of determining the sample using purposive sampling. Data analysis technique using Moderated Regression Analysis. The results showed that the capital structure was able to moderate the giving of Employee Stock Option Program to the performance of the company. Keywords: Employee stock option, program, company performance, capital structure.